Library and information science (LIS) and its related fields as viewed and applied in knowledge management environments in selected government agencies in the Philippines - Zambale, Jerome Paul P. (School of Library and Information Studies, University of the Philippines Diliman, 2012)
Knowledge management (KM) is an internationally emerging field in the Library and Information Science (LIS) profession and it has created new opportunities and challenges to the skills and competencies of library and information professionals. However, the LIS profession in the Philippines seems to be afar from what is happening in the global scenario. Due to this, the researcher took an interest to investigate the LIS roles, skills and competencies are applied and viewed in some KM environments in the country. The study sampled a KM expert through Dr. Serafin Talisayon who is known as the "Father of KM in the Philippines", and government agencies through the KM programs of the National Economic Development Authority (NEDA), Department of Health (DOH), and the House of Representatives, all of which have started to engage in KM in the early 2000s.